求拉普拉斯变换式[img=153x47]17de87a821130d1.png[/img]的原函数为()。
未知类型:{'options': ['', '', '', ''], 'type': 102}
未知类型:{'options': ['', '', '', ''], 'type': 102}
A
举一反三
- 单边拉普拉斯变换[img=420x144]17d60ced1eb01e1.png[/img]的原函数等于()。 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 求下列象函数的拉普拉斯反变换[img=163x95]180367243725eb0.png[/img] 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 求下列象函数的拉普拉斯反变换[img=241x92]180367243cf484e.png[/img] 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 求下列象函数的拉普拉斯反变换[img=140x82]18036724697d8b9.png[/img] 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 求下列象函数的拉普拉斯反变换[img=63x48]180367247c1db86.png[/img] 未知类型:{'options': ['', '', '', ''], 'type': 102}
内容
- 0
求信号[img=164x31]17da70593b9fb5f.png[/img]的单边拉普拉斯变换。 ( ) 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 1
函数[img=117x44]1803b35f4a5d723.png[/img]的拉普拉斯变换[img=143x25]1803b35f534ef03.png[/img] 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 2
1、函数[img=50x39]17de92d20b57451.png[/img]的一个原函数为 ( ) 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 3
1、函数[img=50x39]180317734d7f7b4.png[/img]的一个原函数为 ( ) 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 4
已知[img=109x29]17de74b39ddf1de.png[/img],求单边拉普拉斯变换[img=35x25]17de74b3a987ad0.png[/img] 未知类型:{'options': ['', '', '', ''], 'type': 102}